Responses of a soil-inhabiting collembolan (Entomobrya proxima Folsom) to organic fertilizer addition illustrated by functional traits and gut bacterial community - Yang, Xinyue; Li, Gang; Xiu, Weiming (Frontiers in Microbiology, 2025)
IntroductionOrganic fertilizer offers significant advantages for sustainable agricultural development compared to inorganic fertilizers and is increasingly becoming the predominant fertilizer strategy. Functional traits and gut microbiota of soil fauna are recognized as potential indicators of environmental changes. However, there is a dearth of research examining the correlation between functional traits and intestinal microorganisms in response to organic fertilizer.MethodsIn this study, we selected Entomobrya proxima Folsom, a predominant soil collembolan species found in cropland across North China, as our subject of study. We set treatments with no organic fertilizer (CK) and three different concentrations of organic fertilizer at 1% (O1), 6% (O2), and 10% (O3). Stereomicroscopy and high-throughput amplicon sequencing were employed to elucidate the response of soil fauna to organic fertilizer through host functional traits and associated gut microbial communities.ResultsThe results indicated that the impact of organic fertilizer on the functional traits of collembolans was closely linked to the input concentration. Specifically, low input concentrations positively influenced all functional traits of Entomobrya proxima Folsom; conversely, higher input concentrations exerted an overall detrimental effect. For the gut bacterial community, the addition of organic fertilizer resulted in a significant decrease in abundance, adversely affected α-diversity, and significantly altered the structure of the gut bacterial community compared to CK. However, there was no significant effect of fertilizer concentration on these three parameters. The composition of the gut bacterial community varied due to the addition of organic fertilizer, with significant changes observed in the relative abundances of six phyla and three genera. Furthermore, body length and foreleg length may serve as potential indicators for characterizing the proportions of Alcanivorax and Sphingobacterium of gut bacterial community. Additionally, the assembly process of the gut bacterial community was strongly influenced by the amount of organic fertilizer added; this led to a narrowing niche width that is believed to contribute to an increase in species richness.DiscussionIn conclusion, adding organic fertilizer exerted multiple impacts on soil fauna, with effect sizes related to its concentration. These findings provide insights for conserving soil animals while maximizing their ecological functions and offer perspectives on optimizing sustainable agricultural management practices.